Power of Nonverbal Communication - Kharkevych, Halyna I. (Волинський національний університет імені Лесі Українки, 2024)
Nonverbal communication is a system of signs which are used in the process of communication and differ from language signs by means and a form of their manifestation. For this communication we use our faces, our bodies and our sense of personal space. These means of communication vary from one culture to another, just as verbal languages vary. Nonverbal signs are able to manage the immediate social situation, to express attitudes and communicative intentions and to reveal the cultural values of people.
Keywords: nonverbal communication; body language; facial expressions; vocal characteristics